Estudo metabolômico de plantas alimentícias não convencionais de Sergipe (PANCs) - Santos, Ramon Alves dos (2019)
The metabolomic study of plants is an important tool for the search for new active substances, as it aims to discover all metabolites obtained or modified by an organism and, through multivariate data analysis, define correlations in silic with its biological properties. As vegetable species consumed by the population, such as PANCs (Non-Conventional Food Plants), they are often similar as weeds or "bushes", used for food use in an endemic way, little or almost not sold in open markets, supermarkets, but that it has a potential to be explored. Thus, this work aimed to carry out a metabolomic study of 20 plant species of PANCs consumed in Sergipe, using ultrasound-assisted extraction, direct infusion mass spectrometry in Orbitrap-MS and to evaluate cytotoxicity and antioxidant activity, as well as to correlate this property to possible substances through an in silico study. The common work correlates the cytotoxicity analyzes of extracts to substances with m / z ratio (420.15 positive mode and 423.06 negative mode) at the concentration of 100 μg / mL of plant extracts, substances with m / z ratio (184, 93 positive mode and 507.07 negative mode) at 1000 ug / mL concentration and also correlated the antioxidant activity of plant extracts to substances of m / z ratio (813.51 positive mode and 832.51 negative mode). Therefore, this work demonstrates an important result, as it can be associated with the biological properties of the extracts, in addition to contributing to the identification of plant extracts that can be suggestively toxic to human food.